A simplified model for turbine thrust coefficient and experimental comparison. (January 2020) - Castillo, R; Pol, S; Swift, A
Abstract: A simplified analytical model to estimate yawed-inflow wind turbine thrust coefficient (CT ) based on integrated blade element momentum theory is described and compared with experimental data from a wind tunnel-based wind turbine wake simulator platform. This model, named as I-BEM, requires general inputs such as, chord length at 2/3rd rotor radius from center (c), rotor diameter (D), rotor solidity (σ), tip speed ratio (λ), airfoil lift gradient with respect to angle of attack (d CL /d α ), blade pitch angle (β), and inflow yaw angle (Υ). The model program delivers results instantaneously and does not require high performance computing resources. The model-predicted and measured experimental data comparison showed that CT variation for various Υ and λ can be predicted using a simple program. Primarily, no stall condition is assumed, leading prediction errors under such conditions. Additional model assumptions are outlined in the paper. This simplified analytical model could be utilized for thrust-based wake steering applications where CT measurements are required.